The Intracellular Transporter AtNRAMP6 Is Involved in Fe Homeostasis in Arabidopsis - Li, Jiyu; Wang, Yuerong; Zheng, Lu; Li, Yun; Zhou, Xueli; Li, Jingjun; Gu, Dongfang; Xu, Ending; Lu, Yaping; Chen, Xi; Zhang, Wei (Frontiers in Plant Science, 2019)
Natural resistance-associated macrophage proteins (NRAMPs) have been shown to transport a wide range of divalent metal ions, such as Manganese (Mn), Cadmium (Cd), and Iron (Fe). Iron is an essential micronutrient for plants and Fe deficiency can lead to chlorosis or decreased biomass. AtNRAMP6 has demonstrated the capability to transport Cd, but its physiological function is currently unclear. This study demonstrates that AtNRAMP6 is localized to the Golgi/trans-Golgi network and plays an important role in intracellular Fe homeostasis in the flowering plant genus Arabidopsis. GUS tissue-specific expression revealed that AtNRAMP6 is highly expressed in the lateral roots and young leaves (three to four top leaves) of Arabidopsis. Moreover, knocking out AtNRAMP6 was shown to impair lateral root growth without having a differential effect on the main root under Fe-deficient conditions. Lastly, the expression of AtNRAMP6 was found to exacerbate the sensitivity of the yeast mutant Δccc1 to an excessive amount of Fe. These findings indicate that AtNRAMP6 plays an important role in the growth of Arabidopsis in Fe-deficient conditions.